Urgensi Pendidikan Islam dalam Pembentukan Kesalehan Ekologis di Pondok Pesantren - Muti'atul Chasanah (IIQ An Nur Yogyakarta, 2022)
The environment is an important part of human life. However, the current reality shows that human awareness of their responsibility as khalifah fil ardh has disappeared. So religious values are needed that can regenerate environmental awareness in the community. Moreover, it can integrate the teachings of monotheism, Sufism, and fiqh so that a holistic-integral environmental concept emerges. In this case, pesantren as one of the Islamic educational institutions has an important role in inculcating environmental-based Islamic values. The cultivation of these values ??is an effort to foster ecological piety both within the scope of the pesantren community and the wider community. This study aims to explore more deeply the urgency of Islamic education in the formation of ecological piety in Islamic boarding schools. This study uses a literature review method by using a number of studies by previous researchers as the main data source. The results show that ecological piety or awareness of environmental care can be realized through the implementation of ecologically based Islamic educational values in Islamic boarding schools.